ACO/ARO/AIO-22: external beam radiotherapy combined with endorectal high-dose-rate brachytherapy in elderly and frail patients with rectal cancer : a prospective multicentre trial of the German Rectal Cancer Study Group - Dapper, Hendrik; Fleischmann, Maximilian; Tselis, Nikolaos; Diefenhardt, Markus; Hofheinz, Ralf-Dieter; Weiß, Christian; Grabenbauer, Gerhard G.; Merten, Ricarda; Grosu, Anca-Ligia; Kirste, Simon; Rieken, Stefan; Claßen, Johannes; et al. (Clinical and translational radiation oncology, 2025)
Purpose - Rectal cancer disproportionately affects the elderly population, with more than half of cases diagnosed in individuals aged 70 years or older. Frail patients in this group often face significant challenges tolerating the standard treatment of total mesorectal excision (TME), due to elevated risks of surgical complications and perioperative morbidity. Advances in radiotherapy techniques offer a viable alternative, providing effective tumor control while minimizing treatment-related toxicity. Recent clinical trials, including OPERA and MORPEUS, have demonstrated that dose-escalated radiotherapy, which integrates external beam (chemo)radiotherapy (EBRT) with high-dose-rate endorectal brachytherapy (HDR-BT) or contact X-ray brachytherapy (CXB), can achieve high clinical response rates and facilitate organ preservation in younger, healthier patient cohorts. Building on these findings, the ACO/ARO/AIO-22 study seeks to adapt these innovative approaches to meet the needs of elderly and frail patients with rectal cancer. - Methods/Design - The ACO/ARO/AIO-22 trial is a prospective multicentre controlled trial. Elderly (age ≥70 years) and/or frail patients with non-metastatic rectal adenocarcinoma (cT1-3d N0/+ M0, mrCRM − / +) localized 0-16 cm from the ano-cutaneous line, unable to undergo radical surgery can be included. The initial treatment comprises an external beam radiation (EBRT) regime with 13 × 3 Gy (total: 39 Gy) over a period of two and a half weeks. Following initial restaging 6.5 weeks after completion of EBRT, endorectal HDR-BT will be delivered with 3 weekly fractions of 8 Gy to a total dose of 24 Gy (prescribed at the radial margin of the tumor; with a maximum prescription depth of 10 mm); alternatively, with CXB with 90 Gy in 3 weekly fractions. The primary objective is complete or near complete clinical response (cCR or ncCR) and the second primary endpoint is quality of life (QoL) measured with the EORTC QLQ-ELD14, both at 12 months after treatment start. - Discussion - The ACO/ARO/AIO-22 prospective multicentre trial will evaluate organ preservation rates and QoL after combining EBRT with endorectal HDR-BT in elderly and/or frail patients with rectal cancer. Trial Registration: Clinicialtrials.gov number: NCT06729645.